Integrating technology in Latvian translation education: untranslated medical terminology management practice using online resources and computer-aided translation tools - Dilāns, Gatis (The Journal of Specialised Translation, 2015)
This case study describes a terminology management project for translation students that used a weblog, terminological resources available on the internet and Computer-aided Translation (CAT) tools. The project participants (n=15) were students on a professional translation programme at a university college in the Baltic State of Latvia. During the project, students learned how to find medical terminology translations from Latvian into English that were not present in major Latvian termbases or the Tilde Dictionary. In addition, they were able to manage the terminology in a shared online environment using a free weblog publishing tool from Google, Google Spreadsheets and Microsoft Excel, ultimately converting their bilingual glossary into a termbase with SDL MultiTerm Convert to be used with SDL Trados Studio. The findings of the project study indicate that in order to identify an equivalent term in English, students predominantly used partial transliteration coupled with the Google Autocomplete search prediction technique. Overall, the participants found the project to be a positive experience.